AMMI Canada Position Paper: 2012 Mandatory Influenza Immunization of Health Care Workers. Issue 4 (2012) - Bryce, Elizabeth; Embree, Joanne; Evans, Gerald; Johnston, Lynn; Katz, Kevin; McGeer, Allison; Moore, Dorothy; Roth, Virginia; Simor, Andrew; Suh, Kathryn; Vearncombe, Mary
Abstract : Erratum to "AMMI Canada Position Paper: 2012 Mandatory Influenza Immunization of Health Care Workers" dx.doi.org/10.1155/2013/765639